Assay of ß-glucuronidase activity in intact transformed Aureobasidium pullulans spores - W. Li; L. F. Yourman; S. A. Leong; R. N. Spear; J. H. Andrews (Fungal Genetics Reports, 1997)
Aureobasidium pullulans was transformed with genes encoding ß-glucuronidase (gusA) and GUS expression was assayed fluorometrically. We found that GUS activity in intact, permeabilized fungal cells very closely approximated the sum of the GUS activity in cell-free extracts and pellet fractions. Our results suggest that GUS can be monitored quickly, simply, and quantitatively in intact cells of A. pullulans, and perhaps other fungi, without the need for homogenization.